Thiol-functionalized chitin nanofibers for As (III) adsorption. (9th March 2015) - Yang, Rui; Su, Ying; Aubrecht, Katherine B.; Wang, Xiao; Ma, Hongyang; Grubbs, Robert B.; Hsiao, Benjamin S.; Chu, Benjamin
Abstract: Natural polysaccharide chitin nanofibers, prepared with a series of chemical and mechanical treatments, were used as an absorbent material for arsenic (As(III)) removal. The dimensions of chitin nanofibers, determined by small-angle X-ray scattering (SAXS), were about 6 nm in thickness, 24 nm in width and a few hundred nanometers in length. The chemical/mechanical treatment enabled the chitin nanofiber surface to be charged, thus facilitating the dispersion of nanofibers in aqueous suspension at neutral pH. The large amount of amine groups (1.7 mmol/g) on the nanofiber surface provided opportunities for further modifications, such as formation of amide bonds. In this study, grafting of cysteine was carried out to create adsorption sites for arsenic metal ion (AsO2 − ) removal. The thiol-functionalized chitin nanofibers ([-SH] = 1.1 mmol/g) were characterized by titration, Fourier transform infrared (FT-IR) spectroscopy, energy dispersive spectroscopy (EDS) and scanning electron microscopy (SEM). The arsenic adsorption performance of thiol-modified chitin nanofibers was evaluated under different pH conditions and at different metal ion concentrations, where the maximum adsorption capacity was found to be 149 mg/g at pH = 7.0 using the Langmuir Model. This adsorption capacity was higher than any existing chitin/chitosan-based hydrogel or bead absorbent systems. Graphical abstract: Highlights: Chitin nanofibers had large surface-to-volume ratio and surface functionality. These ultra-fine nanofibers were used as scaffold to remove toxic metal ions. SAXS analysis was applied to demonstrate the nanofiber ribbon structure. A thiol-modification scheme was used to improve the adsorption capability.